Analysis of students' initial scientific literacy of science in elementary school teacher education student - Astri Widyasari; Haryanto Haryanto (Jurnal Inovasi Pendidikan IPA, 2022)
This study aimed to determine the level of scientific literacy possessed by prospective elementary school teachers at Yogyakarta State University. The method used in this research is a qualitative description. The research design used is descriptive quantitative research. The number of subjects in this study was 44 students of PGSD UNY. Data was collected through an online questionnaire survey. Questionnaire data were obtained through question items distributed to respondents in Google Form. The data collection was analyzed using Microsoft Excel and explained as a descriptive explanation. The results of this study indicate that the average scientific literacy ability in scientific competence as a whole is 66.08%, with the achievement category being "good." The percentage of scientific literacy skills achievement on the indicator of identifying scientific problems is 58.33% with the "enough" category. The percentage of achievement on the indicator explaining scientific phenomena is 71.60% with the "good" category. In contrast, the percentage of scientific literacy achievement on scientific evidence indicators is 69.17% in the "good" category. Overall, the literacy level of PGSD UNY students is in the "good" category.